Social networks of rural–urban migrants after residential relocation: evidence from Yangzhou, a medium-sized Chinese city. Issue 6 (18th August 2017) - Huang, Xu; Dijst, Martin; Van Weesep, Jan
Abstract: This paper analyses the effects of residential relocation on China's rural–urban migrants' social networks in light of evidence from Yangzhou, Jiangsu province. Our study contrasts voluntary moves with forced moves driven by demolition-led redevelopment of urban villages. Based on data from a survey conducted between 2012 and 2013, the regression analysis shows that voluntarily relocated migrants are more likely than forced movers to use phone/computer to contact their former neighbours, and communication technology allows them to maintain the frequency of their contact. Furthermore, when moving to a gated neighbourhood, voluntary movers are more likely than forced movers to participate in public activities, to have more contact with new neighbours and thereby to get more help from the residents' committee and new neighbours. The results suggest that forced moves have negative effects on migrants' social networks in the neighbourhood and that the demolition-led redevelopment programmes do not promote the migrants' integration in the city.